2007
DOI: 10.1073/pnas.0607875104
|View full text |Cite
|
Sign up to set email alerts
|

A catalytic beacon sensor for uranium with parts-per-trillion sensitivity and millionfold selectivity

Abstract: Here, we report a catalytic beacon sensor for uranyl (UO 2 2؉ ) based on an in vitro-selected UO 2 2؉ -specific DNAzyme. The sensor consists of a DNA enzyme strand with a 3 quencher and a DNA substrate with a ribonucleotide adenosine (rA) in the middle and a fluorophore and a quencher at the 5 and 3 ends, respectively. The presence of UO 2 2؉ causes catalytic cleavage of the DNA substrate strand at the rA position and release of the fluorophore and thus dramatic increase of fluorescence intensity. The sensor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
481
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 482 publications
(490 citation statements)
references
References 49 publications
(45 reference statements)
9
481
0
Order By: Relevance
“…Upon addition of Na + , NaA43S was cleaved at the rA. Because the melting temperature of the fluorophore-containing arm after cleavage was below room temperature (∼10°C), dehybridization caused the fluorophore to release from its quenchers, resulting in fluorescence increase (47,65). Indeed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon addition of Na + , NaA43S was cleaved at the rA. Because the melting temperature of the fluorophore-containing arm after cleavage was below room temperature (∼10°C), dehybridization caused the fluorophore to release from its quenchers, resulting in fluorescence increase (47,65). Indeed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the goal of selecting Na + -specific DNAzymes, we carried out two parallel experiments using a combination of column-based and gel-based in vitro selection methods reported previously (35,46,47), one in the presence of 135 mM total Na + (selection A) and another in the presence of 400 mM total Na + (selection B). Each selection used a 110-mer oligonucleotide containing a 50-nt random sequence, flanked by conserved sequences at both sides as primerbinding regions for PCR amplification.…”
Section: Resultsmentioning
confidence: 99%
“…A catalytic beacon sensor for U(VI) has also been reported that, under laboratory conditions, showed a sensitivity and selectivity approximately equivalent to the antibody-based sensors reported herein. The beacon sensor has not yet been validated in the field studies and preliminary tests on soil samples required a 20-hour sample extraction [14]. The data presented herein represent the first that has utilized an immunoassay to monitor heavy metal contamination during the progression of an active field experiment.…”
Section: Introductionmentioning
confidence: 99%
“…13 They often recruit divalent metals for catalysis, and in vitro selections can be intentionally performed to evolve DNAzymes that work only in the presence of specific metals. 14 Many divalent metals including Pb 2+ , 15 Zn 2+ , 16 Cu 2+ , 17,18 UO2 2+ , 19 Cd 2+ , 20 and Hg 2+ have been detected using DNAzymes. 21 Recently, important advancements have been made on trivalent metals as well; we isolated and a few lanthanide-dependent DNAzymes.…”
Section: Introductionmentioning
confidence: 99%